2006
DOI: 10.1111/j.1574-6968.2006.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Widespread occurrence of phage-encoded exotoxin genes in terrestrial and aquatic environments in Southern California

Abstract: Many human diseases are caused by pathogens that produce exotoxins. The genes that encode these exotoxins are frequently encoded by mobile DNA elements such as plasmids or phage. Mobile DNA elements can move exotoxin genes among microbial hosts, converting avirulent bacteria into pathogens. Phage and bacteria from water, soil, and sediment environments represent a potential reservoir of phage- and plasmid-encoded exotoxin genes. The genes encoding exotoxins that are the causes of cholera, diphtheria, enterohem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
(41 reference statements)
2
33
0
Order By: Relevance
“…Interactions of host bacteria with temperate bacteriophage also may influence microbial processes. Most notable are virulence factors of many pathogenic bacteria, such as exotoxins, that are phage encoded (7,8). Indirect evidence for a link between quorum sensing and the regulation of the lytic/lysogenic switch appeared recently when quorum sensing was shown to increase Shiga toxin (Stx toxin) production along with the transcription of -like phage genes in E. coli O157:H7 (48).…”
mentioning
confidence: 99%
“…Interactions of host bacteria with temperate bacteriophage also may influence microbial processes. Most notable are virulence factors of many pathogenic bacteria, such as exotoxins, that are phage encoded (7,8). Indirect evidence for a link between quorum sensing and the regulation of the lytic/lysogenic switch appeared recently when quorum sensing was shown to increase Shiga toxin (Stx toxin) production along with the transcription of -like phage genes in E. coli O157:H7 (48).…”
mentioning
confidence: 99%
“…Phage-encoded exotoxins such as cholera toxin, diphtheria toxin, botulinium toxin, and Shiga toxin cause disease in mammals (4). Although these toxins do affect humans and other mammals, these phagecarried exotoxin genes are found at high frequencies in free phages and lysogenic bacteria that are isolated from environments where the presumed corresponding targets are not prevalent (6). These exotoxins kill eukaryotic cells by means of receptors and pathways that are generally conserved among eukaryotic organisms.…”
mentioning
confidence: 99%
“…For instance, Casas et al (19) demonstrated that phage-encoded exotoxins are widespread in water, sediment, and soil. Additionally, sequence analysis revealed a large number of protein secretion systems and virulence gene homologues in marine bacteria (6).…”
mentioning
confidence: 99%